Herpes Simplex Virus 1 Regulatory Protein ICP27 Undergoes a Head-to-Tail Intramolecular Interaction - Hernandez, Felicia P. (American Society for Microbiology (ASM), 2010)
Herpes simplex virus type 1 (HSV-1) regulatory protein ICP27 is a multifunction functional protein that interacts with many cellular proteins. A number of the proteins with which ICP27 interacts require that both the N and C termini of ICP27 are intact. These include RNA polymerase II, TAP/NXF1, and Hsc70. We tested the possibility that the N and C termini of ICP27 could undergo a head-to-tail intramolecular interaction that exists in open and closed configurations for different binding partners. Here, we show by bimolecular fluorescence complementation (BiFC) assays and fluorescence resonance energy transfer (FRET) by acceptor photobleaching that ICP27 undergoes a head-to-tail intramolecular interaction but not head-to-tail or tail-to-tail intermolecular interactions. Substitution mutations in the N or C termini showed that the leucine-rich region (LRR) in the N terminus and the zinc finger-like region in the C terminus must be intact for intramolecular interactions. A recombinant virus, vNC-Venus-ICP27, was constructed, and this virus was severely impaired for virus replication. The expression of NC-Venus-ICP27 protein was delayed compared to ICP27 expression in wild-type HSV-1 infection, but NC-Venus-ICP27 was abundantly expressed at late times of infection. Because the renaturation of the Venus fluorescent protein results in a covalent bonding of the two halves of the Venus molecule, the head-to-tail interaction of NC-Venus-ICP27 locks ICP27 in a closed configuration. We suggest that the population of locked ICP27 molecules is not able to undergo further protein-protein interactions.